ANALISIS HAMBATAN-HAMBATAN INKLUSI KEUANGAN TERHADAP PETANI REMPAH DI SUMENEP - Shela Auliyah Rahmah; Citra Nurhayati (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The rapid development of technology has penetrated various aspects of life, including the financial sector. Financial inclusion remains a significant challenge for farmers in Sumenep due to various underlying issues. This forms the basis for the current research, which aims to investigate the barriers to financial inclusion for spice farmers in Sumenep. The research is essential because it will examine the factors hindering financial inclusion. This study adopts a qualitative research approach with a descriptive research design and employs several research techniques, including interviews, observations, and documentation..